PENDEKATAN KOMPETISI PEMBENTUKAN MASALAH DAN PEMBAHASAN SECARA ESTAFET BERKELOMPOK (PKPMSEB) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MAHASISWA - Armen Armen (Ta'dib, 2011)
This research aimed at figuring out the effect of PKMSEB method toward learning achievement and involvement of Biology Department students in Research Methodology subject. This research employed a classroom action research. The population of the research was 70 students who were taking Research Methodology subject. The data were analyzed by means of descriptive statistics. The findings showed that PKMSEB method improved students’ learning achievement although it was not high. Students’ learning involvement was fairly high. In general, all elements of involvement activity and learning achievement improved, however, the percentage and the score of such improvement were not significant. Scientifically, such improvement can be accepted and the hypothesis was supported.Kata kunci: aktivitas, hasil belajar, kompetisi pembentukan masalah, estafet berkelompok